Structural Changes in 2-Acetoxybenzoic Acid (2ABA) in the Presence of Various Solvents: A Quantum Chemical and Spectroscopic Study - Yılmaz, Mücahit; Kebiroglu, Hanifi (Niyazi BULUT, 2024)
2-Acetoxy benzoic acid (2ABA) can produce structural changes in the molecule when dissolved in different solvents depending on factors such as solvent polarity, Hydrogen bonding and solvent interactions. Therefore, quantum chemical calculations were performed using Gaussian 09: AS64L-G09RevD.01 software. The structural changes of the 2ABA molecule in the presence of solvents were recorded by Fourier Transform Infrared (FT-IR) Spectroscopy in the 4000-0 cm-1 range. Additionally, Nuclear Magnetic Resonance (NMR) Spectroscopy was employed to examine changes in chemical shift values associated with the dissolution of the molecule. In another phase of the study, the geometric parameters of the optimized molecules, atomic charges, intensities of the vibrational bands, and vibrational frequencies were calculated using Density Functional Theory (DFT). These calculations were performed at the DFT/B3LYP level with the LanL2DZ basis set, providing a detailed analysis of solvent effects at the molecular level. This study offers significant insights into the interactions of solvent environments with molecular structures and contributes to potential drug development processes.
Keywords: Atomic and Molecular Physics; Atom ve Molekül Fiziği; Molecular Imaging; Moleküler Görüntüleme